Climate change framings and linkages across international organizations - Karina Shyrokykh; Lisa Dellmuth (Earth System Governance)
As climate change is becoming an ever more pressing global policy challenge, the linkages of climate change to other issue areas are diversifying. This article seeks to explain why some climate linkages are more likely to spread across international organizations (IOs) than others. Drawing on organizational and framing theories, we argue that the framing of climate linkages affects how such linkages disseminate across IOs. Distinguishing between three framings of climate change––technical, emotional and emergency––we develop and test novel hypotheses about the effects of framing climate linkages on their spread on social media. We use an original dataset on the dissemination of climate linkages on the social media platform Twitter (currently X) among eight IOs with a global mandate during the period 2008–2019. The results suggest that both the characteristics and the framing of climate linkages influence their spread across the studied IOs, as we find, in the context of the climate-development and climate-disaster risks linkages, that technical and emotional framings affect how linkages spread across several United Nations agencies. In all, we show the importance of the interplay between climate change linkages and the framings of these linkages for their spread across IOs.